2002
DOI: 10.1038/sj.tpj.6500087
|View full text |Cite
|
Sign up to set email alerts
|

Specific and overlapping functions of the nuclear hormone receptors CAR and PXR in xenobiotic response

Abstract: The products of the cytochrome P450 (CYP) genes play an important role in the detoxification of xenobiotics and environmental contaminants, and many foreign chemicals or xenobiotics can induce their expression. We have previously shown that the nuclear hormone receptor CAR (Constitutive Androstane Receptor, NR113) mediates the well studied induction of CYP2B10 gene expression by phenobarbital (PB) and 1, 4-bis-[2-(3, 5,-dichloropyridyloxy)] benzene (TCPOBOP). We have used the CAR knockout mouse model to explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
167
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(179 citation statements)
references
References 30 publications
9
167
3
Order By: Relevance
“…1). Previous data have demonstrated that the potent CAR agonist TCPOBOP only induces Cyp2a4 in males and in a CAR-dependent fashion (Wei et al, 2002). Statistically significant increases in Cyp2a were not observed by Western blotting or testosterone 6α-hydroxylase activity in males.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…1). Previous data have demonstrated that the potent CAR agonist TCPOBOP only induces Cyp2a4 in males and in a CAR-dependent fashion (Wei et al, 2002). Statistically significant increases in Cyp2a were not observed by Western blotting or testosterone 6α-hydroxylase activity in males.…”
Section: Discussionmentioning
confidence: 75%
“…Dexamethasone downregulates the female-predominant Cyp3a41 in a PXR-dependent manner, while male mice did not demonstrate downregulation of any Cyp3a subfamily members (Anakk et al, 2004). In addition, the CAR activators, phenobarbital and 1,4-bis-[2-(3,5-dichloropyridyloxy)]benzene (TCPOBOP) demonstrate male-specific Cyp2a4 induction (Wei et al, 2002). Lastly, St. John's wort mediated induction of CYP3A4 is greater in human females than males (Gurley et al, 2002).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Mice with genetic ablations of CAR and PXR have significantly reduced inducibility of CYPs by a variety of drugs [8,9]. Whereas these two receptors share some common ligands and also have an overlapping target gene pattern [10][11][12][13], the mode of activation for CAR and PXR is quite different [14]. PXR is located in the nucleus, it has a low basal activity and is highly activated upon ligand binding [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] In mice that are deficient in either of these genes, they have clear, select and impressively debilitated capabilities of detoxifying xenobiotics and endobiotics. [13][14][15] This is most evident in the regulation of the central P 450 detoxifying enzyme Cyp3a4 (Cyp3a11 in mice), which is strongly activated by both CAR and PXR ligands, and reduced in activity in CAR Ϫ/Ϫ and PXR Ϫ/Ϫ mice. Moreover, these two NRs are critical to the handling of bile acids, notably lithocholic acid.…”
mentioning
confidence: 99%